TEACHER OF FACULTY OF FOREIGN LANGUAGES PHILOLOGY - Temirova Hayotxon Bayramali qizi (Journals Park Publishing, 2022)
It is of great importance to teach English language learners in Uzbekistan to pronounce every sound like a native speaker. It is unavoidable that EFL learners will be influenced by a variety of Uzbek dialects, which may cause difficulties in English pronunciation. Some EFL learners speak Uzbek English with phonetic errors that will cause difficulties in communication. Totally 37 works have been found to be useful for methodological basis. However, given research by Uzbek linguists seem to neglect to explain how and why negative transfer of regional dialects on English pronunciation occurs and deeper explanations seem to be neglected. Besides, there are quite few of them. This paper explains the influences of “qipchoq” dialect on English pronunciation of EFL learners in Uzbekistan and aims to help EFL teachers realize the importance of the effects of dialects on English education for Uzbek students. This work will be part of the literature of the field which is being studied and it will benefit the future researchers and English language teachers who are willing to analyze the difference of phonetic and phonological mistakes among dialect speakers of Uzbekistan.
Keywords: Pronunciation, positive transfer, negative transfer, sound, dialects, phonetics, consonants, vowels.